Acid-Sensing Ion Channels as Potential Therapeutic Targets in Neurodegeneration and Neuroinflammation - Audrey Ortega-Ramírez; Rosario Vega; Enrique Soto (Mediators of Inflammation)
Acid-sensing ion channels (ASICs) are a family of proton-sensing channels that are voltage insensitive, cation selective (mostly permeable to Na+), and nonspecifically blocked by amiloride. Derived from 5 genes (ACCN1–5), 7 subunits have been identified, 1a, 1b, 2a, 2b, 3, 4, and 5, that are widely expressed in the peripheral and central nervous system as well as other tissues. Over the years, different studies have shown that activation of these channels is linked to various physiological and pathological processes, such as memory, learning, fear, anxiety, ischemia, and multiple sclerosis to name a few, so their potential as therapeutic targets is increasing. This review focuses on recent advances that have helped us to better understand the role played by ASICs in different pathologies related to neurodegenerative diseases, inflammatory processes, and pain.